Discrete element modelling of permanent pavement deformation in granular materials - Cai, Wei (2015)
The permanent deformation of a pavement due to vehicle load is one of the important factors affecting the design life as well as the maintenance cost of a pavement. For the purpose of obtaining a cost-effective design, it is advisable to predict the traffic-loadinduced permanent pavement deformation. The permanent deformation in pavements (i.e. rutting) can be classified into three categories, including the wearing of the asphalt layers, compaction, and shear deformations. In the present study, discrete element analyses have been performed to predict the permanent deformation of a pavement when subjected to moving wheel loads. Note that the wearing of the asphalt layers has been disregarded.